Activities of Local Authorityes in the Uzbekistan SSR (1930s off XX Century) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article provides information about the changes in the activities of local authority’s in the Uzbek SSR in the 1930s, the transition from a three-tier local government to a two-tier system of district and village soviets, and the formation of neighborhood(mahalla) committees based on the formation of the charter of neighborhood committees in cities.